Diversity, Equity, and Inclusion Initiatives of Communication Sciences and Disorder Programs Across the United States. - Stewart, Jessica R.; Mishra, Srikanta (Perspectives of the ASHA Special Interest Groups, 2022)
Purpose: The purpose of this pilot study is to begin exploring the diversity, equity, and inclusion (DEI) initiatives being implemented by communication sciences and disorders (CSD) programs at various universities across the United States with the intent to guide and support future research studies. Method: Publicly available data of DEI initiatives used by CSD programs across the United States were utilized for this study. A three-step procedure was used to explore reported initiatives. First, responses were reviewed to determine whether the reported initiatives were focusing on diversity, equity, and/or inclusion. Second, each independent initiative was reviewed, and common themes were identified. Third, the reported impact of DEI initiatives on CSD programs was explored. Results: This study produced four major findings related to DEI initiatives in CSD programs: (a) The majority of CSD programs included in this study reported use of DEI initiatives focusing on inclusion; (b) CSD programs included in this study reported implementation of DEI initiatives that fall into seven themes; (c) CSD programs included in this study reported DEI initiative impact on students and a reduced number of programs reported impact on faculty, staff, and the community; and (d) the DEI initiatives of CSD programs included in this study appeared to vary according to university-level factors. Conclusions: There is a dearth of information relating to the use of DEI initiatives being implemented by CSD programs. The results of this pilot study can be used to implement future studies and programs with the ultimate goal of improving DEI in the fields of speech-language pathology and audiology.